Stabilizing the System of Mortgage Finance in the United States - Koss, Richard (IMF Working Papers; Working Paper ;, 2017)
It has been over a decade since the peak of house prices in the US was attained, and while there has been a concerted regulatory response to the subsequent collapse, the two Government Sponsored Enterprises (GSEs) remain in conservatorship. While this action served to forestall a deeper crisis at the time, over the past several years risks related to the system of mortgage finance can be seen building across several dimensions that need to be addressed. While reforms to the GSEs are an important part of dealing with these concerns, this paper argues that broader changes need to be made across the entire mortgage landscape to stabilize the system, even before the final state of the GSEs is fully determined.